Data on Stop Codon Usage in Bacteria and Its Correlation with Release Factor Abundance - Korkmaz, Gürkan (Uppsala University, 2016)
We present a comprehensive analysis of stop codon usage in bacteria by analyzing over eight million coding sequences of 4684 bacterial sequences. Using a newly developed program called "stop codon counter," the frequencies of the three classical stop codons TAA, TAG, and TGA were analyzed, and a publicly available stop codon database was built.

Datafiles contain:
1) Complete data set of stop codon usage of all analyzed sequences as described in the publication "Comprehensive Analysis of Stop Codon Usage in Bacteria and Its Correlation with Release Factor Abundance" by Korkmaz et al (2014).

2) The Java program that was used for the analysis of the coding sequences. Execute the file in Program\ProjectStopCodonCounter\dist


The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av katalogposten för information om data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on Stop Codon Usage in Bacteria and Its Correlation with Release Factor Abundance
Comprehensive Analysis of Stop Codon Usage in Bacteria and Its Correlation with Release Factor Abundance
Keywords: molecular biology; molekylärbiologi; bacteria; bakterier; biochemistry; biokemi; Biochemistry; Biokemi; Molecular Biology; Molekylärbiologi